(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
Social security is a topic widely discussed around the world, especially in South America. This research focused on the social security systems of Brazil and Chile, seeking to answer the following question: how do the different approaches to social security in these countries impact the guarantee of fundamental rights and the protection of citizens? The research used the deductive method, based on a bibliographic analysis of the significant changes that social security has undergone over the decades. The results indicate that social security can be positive, by guaranteeing fundamental rights and protecting citizens, but it can also be negative, when poorly implemented, resulting in disparities and injustices. The research concluded that social security requires moderation, supervision, and continuous evolution to ensure the maintenance of a republic and, consequently, of a democracy. Human finitude and the need for state guardianship in old age reinforce the importance of social security as a universal right. Thus, social security should be seen not only as a protection system for old age, but as an essential pillar of any democratic society. This study concludes that it is a fundamental right that guarantees human dignity, equality, life, and health, and should be protected and strengthened to ensure the well-being of all citizens.